Development of unilateral crochet device fabricated through additive manufacturing (Human Factors in Design, 2023)
Assistive Technologies (AT) must be specified beyond their functionality goal and consider the factors in which they will be applied, specifically cost and access. The objective was to develop a unilateral crochet device through additive manufacturing. Considering the demands of a hospitalized patient, necessary measurement and positioning were identified, a prototype model was designed through CAD and later manufactured through a 3D printer. The device was successfully tested by two Occupational Therapy students with previous knowledge on bimanual crochet. The AT should go through patient testing in the future.
Keywords: unilateral crochet; additive manufacturing; 3D printing